2017
DOI: 10.1161/circep.116.004331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Late Sodium Current Blockade on Ventricular Refibrillation in a Rabbit Model

Abstract: Background-After defibrillation of initial ventricular fibrillation (VF), it is crucial to prevent refibrillation to ensure successful resuscitation outcomes. Inability of the late Na + current to inactivate leads to intracellular Ca 2+ dysregulation and arrhythmias. Our aim was to determine the effects of ranolazine and GS-967, inhibitors of the late Na + current, on ventricular refibrillation. Methods and Results-Long-duration VF was induced electrically in Langendorff-perfused rabbit hearts (n=22) and termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…An interesting finding was the beneficial impact of ranolazine in post‐VF animal models . Particularly, ranolazine showed to reduce the susceptibility to subsequent refibrillation, but further testing in cardiac arrest models is needed . An interesting finding is that ranolazine has a potent suppressant effect on both re‐entrant and multifocal VF at concentrations considered therapeutic in humans …”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding was the beneficial impact of ranolazine in post‐VF animal models . Particularly, ranolazine showed to reduce the susceptibility to subsequent refibrillation, but further testing in cardiac arrest models is needed . An interesting finding is that ranolazine has a potent suppressant effect on both re‐entrant and multifocal VF at concentrations considered therapeutic in humans …”
Section: Discussionmentioning
confidence: 99%
“…During VF, optical mapping was performed to evaluate VF organization at two time‐points (0 and 4 minutes of VF); as a surrogate for VF organization, the number of Ca 2+ wavefronts during VF were quantitated, as described previously …”
Section: Methodsmentioning
confidence: 99%
“…The detailed methodology for Ca 2+ optical mapping has been described in our previous studies. 3,11 Dye fluorescence was excited using a xenon light source (Moritex, Saitama, Japan) and a 530-nm green filter (Semrock, Rochester, NY) and the emission light was bandpass filtered at 585/40 nm. The fluorescence was recorded with a high-speed CMOS camera (Ultima-L; SciMedia, Costa Mesa, CA).…”
Section: Ca 2+ Mappingmentioning
confidence: 99%
“…The Ca i alternans suppression and Ca i TD 80 shortening were reported to reduce the susceptibility to subsequent refibrillation in a long-standing VF rabbit model. [24] Additionally, calsequestrin 2 is the It was reported that cardiac IR injury is accompanied by a marked reduction in SR Ca 2+ -pump ATPase, Ca 2+ -uptake and Ca 2+ -release activities, and the mRNA levels for SR Ca 2+ -handling proteins such as SERCA2a, ryanodine receptor, calsequestrin and phospholamban were decreased in the ischemiareperfused heart as compared with the non-ischemic control. [28] Our data also shows that protein expression of pThr17-phospholamban, calsequestrin 2, and SCN5A was significantly decreased in the IR zone in diabetic mouse hearts, and ranolazine ameliorated the downregulation of these proteins.…”
Section: Ranolazine Administration Improves Ca Dynamics In the Ir Zonementioning
confidence: 98%